Planning and Macrostructural Elements for a Multilingual Culinary Dictionary of Gabonese Languages - Ompoussa, Virginie; Ndinga-Koumba-Binza, Hugues Steve (Lexikos, 2015)
This paper is an account of an ongoing dictionary project. It aims to outline the main features of the planned dictionary. The project is a first of its kind in Gabonese lexicography. The current paper gives a description of the data collection and sources as well as the macrostructural issues of the forthcoming dictionary. The paper starts with a brief outline of the project background, needs and interests.